Real-time in situ detection and quantification of bacteria in the Arctic environment - Linda Powers; Walther R. Ellis; Christopher R. Lloyd (Journal of Innovative Optical Health Sciences, 2014)
At present, there are no methods that determine the total microbial load on an abiotic substrate in real time. The utility of such a capability ranges from sterilization and medical diagnostics to the search for new microorganisms in the environment and study of their ecological niches. We report the development of a hand-held, fluorescence detection device and demonstrate its applicability to the field detection of Arctic bacteria. This technology is based on the early pioneering work of Britton Chance which elucidated the intrinsic fluorescence of a number of metabolites and protein cofactors in cells, including reduced pyridine nucleotides, cytochromes and flavins. A PDA controls the device (fluorescence excitation and data collection) and processes the multiwavelength signals to yield bacterial cell counts, including estimates of live cells, dead cells and endospores. Unlike existing methods for cell counting, this method requires no sample contact or addition of reagents. The use of this technology is demonstrated with in situ measurements of two sub-glacial microbial communities at sites in Palander and colonized surface rocks in the Bockfjord Volcanic Complex during AMASE 2008 (Arctic Mars Analog Svalbard Expedition). The total bacterial load on the interrogated sample surfaces ranged from < 20 cells/cm2 to > 109 cells/cm2.